2016
DOI: 10.1007/s10900-016-0217-3
|View full text |Cite
|
Sign up to set email alerts
|

American Heart Association’s Ideal Cardiovascular Health Metrics in Under-Represented Asian Americans

Abstract: The American Heart Association’s ideal cardiovascular health score is based on 7 cardiovascular health metrics to measure progress toward their Impact Goal of reducing cardiovascular disease by 20 % before 2020. This study applied this construct to assess cardiovascular health in a sample of Asian Americans. Convenience sampling methods were used to enroll self-identified Asian American’s over the age of 18 years who were attending community health fairs across the greater Philadelphia and urban areas of New J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…On top of that, even gender can be skewed. For example, Patterson, et al [15] reported a research study involving 82% female in a sample consisting of 45% Vietnamese, 38% Chinese, and 17% Korean. Moreover, even in cases when the research sample is predominantly one to three Asian American ethnic groups, the findings are applied to all Asian Americans.…”
Section: Aggregating Asian American Ethnic Groups Into a Single Ethnimentioning
confidence: 99%
See 1 more Smart Citation
“…On top of that, even gender can be skewed. For example, Patterson, et al [15] reported a research study involving 82% female in a sample consisting of 45% Vietnamese, 38% Chinese, and 17% Korean. Moreover, even in cases when the research sample is predominantly one to three Asian American ethnic groups, the findings are applied to all Asian Americans.…”
Section: Aggregating Asian American Ethnic Groups Into a Single Ethnimentioning
confidence: 99%
“…Moreover, even in cases when the research sample is predominantly one to three Asian American ethnic groups, the findings are applied to all Asian Americans. As such, if a sample of hundreds to thousands of Asian Americans was predominantly one ethnic group, with only few participants from other Asian American ethnic groups, the results of the thousands (the predominant Asian American group) were reported as being representative for all members of the Asian American group represented by very few individuals [4,10,15]. The incorrect extrapolation of data from one Asian American ethnicity was commented on by Holland and Palaniappan [16].…”
Section: Aggregating Asian American Ethnic Groups Into a Single Ethnimentioning
confidence: 99%
“…Filipinos face high rates of heart disease, type 2 diabetes, and hypertension compared to non-Hispanic Whites and other Asian American subgroups [2,3,4,5,6]. Additionally, Koreans face higher rates of hypertension, hypocholesteremia, cancer, and diabetes [7,8]. Hypertension, or high blood pressure, is a common chronic disease reported in Filipinos and Korean Americans and frequently is associated with poor dietary and lifestyle factors, including physical inactivity and elevated stress [1,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, or high blood pressure, is a common chronic disease reported in Filipinos and Korean Americans and frequently is associated with poor dietary and lifestyle factors, including physical inactivity and elevated stress [1,9,10,11,12,13]. Studies investigating hypertension prevalence in these groups found rates ranging from 48−67.5% in Filipinos and 30.8−53% in Koreans [8,14,15,16,17,18]. Hypertension prevention and management are important issues that require greater attention in these populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation